Diagnóstico de los sistemas de siembra de soya (Glycine max L.) en la zona de Pueblo Nuevo - Cortez Carpio, Lenin Wilson (2020)
Soy is a legume of Asian origin, its composition is high protein content and medium fat, consumed as a source of nutrients in human food and in recent decades it has been used as an important input to produce feed for livestock on a larger scale of poultry and pigs. In human nutrition, it is consumed in its basic form of grass or in processed foods such as flavor additives, soy meat, oils are extracted due to their fat content, it is highly recommended. There is also activity in the soybean meal production industry and its derivatives. Currently, the results obtained in the survey and analysis of information for the year 2016 indicate that the national average objective yield of soybeans was 2.02 tons per hectare. Through the development of this document, it is intended to publicize the diagnosis of soybean planting systems in the Pueblo Nuevo area, in order to provide relevant information that defines the importance of the types of crops in soybean cultivation. Ignorance of the sowing systems and their importance is the main problem during the development of the crop and execution of the cultural tasks, because it influences the yield, nutritional content and planting population. The planting density will depend on the variety of soybeans and the type of planting required. Currently in soybean cultivation, various sowing systems stand out, the main ones being direct sowing by row or furrow and broadcast, which is distributed evenly by the machinery. In the same way, manual sowing is carried out where a greater quantity of seed is required. In the case that three or four seeds are sown, it is necessary to clarify afterwards, in order to leave vigorous soybean plants. In turn, prior to sowing, the seed must be selected, choosing the one that is in the best conditions in order to improve the quality of the soybean. Among the main alternatives is the recognition of the area to be sown or available for soybean cultivation.